Accidental microembolic signals: prevalence and clinical relevance. Issue 1 (December 2016) - Chen, Jie; Hu, Ying-Huan; Gao, Shan; Xu, Wei-Hai
Abstract Background The purpose of this study was to examine the occurrence of accidental microembolic signals (MES) and its clinical relevance in patients receiving routine transcranial Doppler (TCD) examinations. Methods We retrospectively reviewed our institutional TCD database (from January 2007–November 2012). The arteries with positive MES, the presumed sources of emboli and the clinical backgrounds were analyzed. Results A total of 10, 067 patients received routine TCD examinations in our laboratory during the research period. MES were detected in 98 arteries of 78 patients, with a frequency of 0.77 % of all the recruited patients. A high percentage of MES (64.3 %) were detected in MCAs. Sixty five (83.33 %) accidental emboli were from arterial sources, including atherosclerotic cerebral or carotid artery stenosis (n = 45), moyamoya disease (n = 11), intracranial arteries (n = 3) and Takayasu arteritis (n = 3). Thirteen (16.67 %) emboli were from cardiac sources, including atrial fibrillation (n = 3), artificial valves (n = 8), infective endocarditis (n = 2), patent foramen ovale (n = 2), and systemic lupus erythematosus (n = 1). In artificial valves disease, all patients with MES were asymptomatic, while in atherosclerotic cerebral or carotid artery stenosis, 66.67 % (n = 30) patients with MES were symptomatic. In different diseases with accidental MES, the proportion of symptomatic patients and asymptomatic patients were different (p < 0.001). Conclusions MES are not uncommon during routine TCD examinations, the clinical value of which varied in different diseases.